The relationship between use of complementary and alternative medicine and health literacy in chronically ill outpatient cases: a cross-sectional study in southeastern Iran - Dehghan, Mahlagha; Rad, Mahla Mohebi; Lari, Leyla Ahmadi; Ghorbani-nejad, Behnam; Mohebi-Rad, Milad (Frontiers in Public Health, 2023)
Background Chronically ill outpatient cases use a variety of complementary and alternative medicines due to their diseases and therapeutic complications. Chronic condition, quality of life, and health literacy all affect the use of complementary medicine among chronically ill outpatient cases. Health literacy helps patients make fully informed decisions about the use of complementary and alternative medicine. This study aimed to investigate the relationship between complementary and alternative medicine and health literacy in chronically ill outpatient cases. Method This cross-sectional analytical-descriptive study was conducted on 400 chronically ill outpatient cases referred to medical centers affiliated to Kerman University of Medical Sciences. Convenience sampling was used. Research tools included the complementary and alternative medicine questionnaire and the health literacy questionnaire. SPSS25 was used to analyze data. Results The mean use of complementary and alternative medicine in a recent year was 16.75 ± 7.89, which was lower than the mid-point of the questionnaire (84). Prayer, medicinal plants, vitamin supplements, music therapy, and art therapy were the mostly used complementary and alternative medicine methods. The most common reasons for using complementary medicine were to reduce physical complications and improve anxiety and stress. The mean satisfaction with the use of complementary and alternative medicine was 34.96 ± 6.69. The mean health literacy score was 67.13 ± 19.90. Decision-making and the use of health information had the highest mean score among the dimensions of health literacy, whereas reading skills received the lowest mean score. We found a significant and direct relationship between the use of complementary and alternative medicine, health literacy, and all its dimensions. Conclusion The study results showed that health literacy predicted the use of complementary and alternative medicine. Health education and promotion programs may be useful for improvement of health literacy in the community.